Game Based Learning to improve mathematics conceptual understanding / Muniroh Hamat - Hamat, Muniroh (Unit Penerbitan JSKM, 2023)
In many respects, computer games have infiltrated everyday life. Many studies and designed systems include features in the structure of the game that draw attention and fun, consequently enhancing student motivation in the field of educational learning. We shall provide many theoretical reasons supporting the benefits of using games in education and learning in this study. We will also distinguish between methodologies such as Game Based Learning (GBL), educational games, and Gamification in education. A clear definition of this new term will be offered, along with an explanation of the potential impacts on teaching and learning. Games can make learning concepts more enjoyable and provide a platform for students to improve their creative thinking. Games are frequently used as a learning trigger, stimulating conversation about the concept of learning among students after they have completed a game. Some new teaching methods, such as Games Based Learning and Gamification, can be used to boost the learning spirit of students of all ages. The purpose of this study is to identify research methods and the fields that the chosen articles on game-based learning cover. The fundamentals and characteristics of game-based learning, an overview of game-based learning from prior studies, the application of game-based education for students and teachers, conclusions, and suggestions for further study are also included in this article.